Factors Affecting Health-Related Quality of Life and Physical Activity after Liver Transplantation for Autoimmune and Nonautoimmune Liver Diseases: A Prospective, Single Centre Study - Katarzyna Kotarska; Ewa Wunsch; Agnieszka Kempińska-Podhorodecka; Joanna Raszeja-Wyszomirska; Dimitrios P. Bogdanos; Maciej Wójcicki; Piotr Milkiewicz (Journal of Immunology Research)
Background/Aim. With the improvement of the outcomes after liver transplantation (LTx), health-related quality of life (HRQoL) and physical activity are becoming significant outcome parameters. We prospectively assessed these parameters in patients with autoimmune and nonautoimmune liver disorders undergoing LTx. Materials and Methods. Patients (n=107) were subdivided into 3 groups depending on the time after LTx: group-A (n=21): 6–12 months; group-B (n=48): 13–36 months; and group-C (n=38): >37 months. SF-36 and IPAQ were applied in HRQoL and physical activity assessment. Results. Females had impaired HRQoL in most SF-36 domains. Younger patients showed higher scores at SF-36 physical functioning domain but IPAQ was not influenced by age. Group-B had higher general health and physical component summary than group-A (P=0.037, P=0.04, resp.) and total IPAQ than group-C (P=0.047). The sitting time domain was longer in group-A than in group-B and group-C (P=0.0157;  P=0.042, resp.). Employed patients had better HRQoL and higher physical activity than those not working. SF-36 and IPAQ were unrelated to the autoimmune etiology of liver disease. Conclusions. These findings show that female and unemployed patients have worse HRQoL, while gender and age at LTx time do not affect IPAQ’s physical activity. The autoimmune etiology of liver disease does not influence HRQoL and physical activity after LTx.